A Domino Reaction of Pyridinium Salts: Efficient Synthesis of 4, 5‐Disubstituted 1, 2, 3‐(NH)‐Triazoles. Issue 18 (14th May 2018) - Wu, Guang‐Long; Wu, Qin‐Pei
Abstract: A one‐pot mild and metal‐free procedure for efficient synthesis of 4, 5‐disubstituted 1, 2, 3‐( NH )‐triazoles has been developed through the sequentially reaction of pyridinium salts with aldehydes and sodium azide. In the presence of L‐proline, a key intermediate, an olefinic pyridinium‐salt, is in situ generated via coupling of pyridinium salts with aldehydes and cyclizes with azide ion to form a triazole ring. Abstract : Efficient synthesis of 4, 5‐disubstituted 1, 2, 3‐(NH)‐triazoles is performed through the sequentially reaction of pyridinium salts with aldehydes and sodium azide.